2017
DOI: 10.18203/2320-6012.ijrms20173964
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of knowledge, attitude and practice regarding rabies and its prevention among construction workers: a cross-sectional study in Berhampur, Odisha

Abstract: Background: Rabies is a viral zoonosis and human infection usually occurs following transdermal bite or scratch by an infected animal. It is one of the most dangerous and completely preventable diseases. Construction workers are vulnerable to animal bites. So, this study was undertaken to study the knowledge, attitude and practice regarding animal bite and rabies among construction workers.Methods: A cross sectional study was done in campus of MKCG medical college, Berhampur, Odisha, India. Data was collected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
15
6

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 3 publications
2
15
6
Order By: Relevance
“…6 Tripathy et al reported that 98.2% participants knew that dog was the source of infection. 11 The observation was found inconsistent with our study findings (39.5%). Regarding transmission of rabies, 60.5% respondents knew correctly as compared to study done in Puducherry, where 98.9% respondents answered that rabies can be transmitted by animal bites.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…6 Tripathy et al reported that 98.2% participants knew that dog was the source of infection. 11 The observation was found inconsistent with our study findings (39.5%). Regarding transmission of rabies, 60.5% respondents knew correctly as compared to study done in Puducherry, where 98.9% respondents answered that rabies can be transmitted by animal bites.…”
Section: Discussioncontrasting
confidence: 99%
“…6 In our study, only literacy was found associated with level of knowledge on rabies but Tripathy et al study reported that KAP score was significantly associated with age, sex, education and residence whereas Chopra et al study reported that sex, religion and marital status were significantly associated with knowledge level. 11,12…”
Section: Discussionmentioning
confidence: 99%
“…14 In the present study 66.66% of the study population think that vaccination of dog is necessary, where as in a study by Tripathy et al 70.2% participants and in a study by Chandan et al 81% participants think that it is necessary to vaccinate dogs. 11,12 In the present study 16.66% apply lime/turmeric to the wound which is similar to the studies by Valekar et al (19.3%) and Chandan et al in Dharwad (20%), which means still there are many traditional practices going on everywhere in the community. 11,14 In the present study 95% of the population prefer to consult a doctor if bitten by dog, where as it is very less in a study by Kamble et al (27.6%), 77% prefers to consult a doctor in a study by Chandan et al 11,13 In the present study, only 10.8% of the participants said that they get information from health workers which is lower compared to a study by Chandan et al (34%).…”
Section: Discussionsupporting
confidence: 88%
“…In the present study 90% of the people opine that dog bite is dangerous, almost similar (85%) in a study conducted by Chandan et al in Dharwad, where as in a study by Tripathy et al, it is 62.5%. 11,12 In the present study only 30% of the study participants were aware of the need of washing of the wound after bite, in a study by Panesar et al in Delhi 22.1% were aware, in contrast to the study by Valekar et al in Maharashtra, 48.6% and Chandan et al in Dharwad, 73% were aware of the same. 11,13,14 In the present study 71.6% of the participants were aware about the vaccine for dog bite, and is almost similar to study by Chandan et al (67%) in Dharwad where as it was very much high(95.8%) in a study by Valekar in Maharashtra.…”
Section: Discussioncontrasting
confidence: 66%
“…A large number of clinical studies have been conducted worldwide to highlight this key aspect. 4,5,6,7,8 Global statistics have shown that 90% of human deaths due to rabies occur in children. Deaths in children occur because they like playing with dogs and lack awareness about transmission of rabies by dogs.…”
Section: Discussionmentioning
confidence: 99%